Efffect of the ABCC3 –211C/T polymorphism on clopidogrel responsiveness in patients with percutaneous coronary intervention. (29th July 2013) - Zou, Jian‐Jun; Fan, Hong‐Wei; Chen, Shao‐Liang; Tan, Jie; He, Bang‐Shun; Xie, Hong‐Guang
Summary Multidrug resistance protein 3 (MPR3), encoded by the ATP‐binding cassette, subfamily C (CFTR/MRP), member 3 (ABCC3) gene, functions as an important drug efflux transporter. The ABCC3 –211C/T polymorphism is associated with decreased MRP3 mRNA expression, and low MRP3 mRNA expression is associated with increased clopidogrel response in patients. The aim of the present study was to determine whether the –211C/T polymorphism is associated with altered antiplatelet effects and clinical outcomes in clopidogrel‐treated patients. A subcohort of 249 patients not carrying the CYP2C19*2, *3 or *17 variant was identified from a total of 617 consecutive clopidogrel‐treated patients undergoing percutaneous coronary intervention and then categorized into three groups on the basis of their ABCC3 –211C/T genotype. Baseline data, clinical characteristics and DNA samples were collected for all patients. Light transmittance aggregometry was used to determine ADP‐induced maximum platelet aggregation (MPA) in blood samples obtained from patients on Day 3 after starting daily clopidogrel maintenance doses. Genotyping of CYP2C19*2, *3 and *17 variants and the ABCC3 –211C/T polymorphism was performed using matrix‐assisted laser desorption ionization time‐of‐flight (MALDI‐TOF) mass spectrometry. The primary clinical end‐point was a definite stent thrombosis (ST) episode, whereas secondary end‐points were other major adverse cardiovascular events within 12 months after stenting. There were no differences in MPA values according to ABCC3 –211C/T genotype. A multiple linear regression model revealed that the ABCC3 –211C/T polymorphism was not independently associated with ADP‐induced MPA measurements; a multiple logistic regression model revealed that carrying the ABCC3 –211C allele was not associated with the risk of developing an ST event in clopidogrel‐treated patients not harbouring CYP2C19*2, *3 and *17 variants. In conclusion, the ABCC3 –211C/T polymorphism seems not to be associated with altered antiplatelet effects and clinical outcomes in clopidogrel‐treated patients.